Metformin‐induced encephalopathy: the role of thiamine. Issue 2 (7th February 2018) - McGarvey, Caoimhe; Franconi, Catherine; Prentice, David; Bynevelt, Michael
Abstract: A case of metformin encephalopathy is presented in a patient on haemodialysis for end‐stage diabetic renal failure. The patient presented with frequent falls and clinical signs of Parkinsonism, on a background of recent anorexia and significant weight loss. Magnetic resonance imaging showed bilateral, symmetrical abnormalities centred on the lentiform nuclei. Metformin was withheld and signs and symptoms quickly resolved. We hypothesise that metformin may cause thiamine deficiency in patients with end‐stage renal failure resulting in a specific metabolic encephalopathy.